2017
DOI: 10.1371/journal.pone.0182428
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the effectiveness of vocal features in early telediagnosis of Parkinson's disease

Abstract: The recently proposed Parkinson's Disease (PD) telediagnosis systems based on detecting dysphonia achieve very high classification rates in discriminating healthy subjects from PD patients. However, in these studies the data used to construct the classification model contain the speech recordings of both early and late PD patients with different severities of speech impairments resulting in unrealistic results. In a more realistic scenario, an early telediagnosis system is expected to be used in suspicious cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 43 publications
1
34
0
7
Order By: Relevance
“…Research has now started to use digital technology to gather bodily sounds (e.g., digital stethoscopes) and run automatic analysis on the data [24], for example for wheeze detection in asthma [18,23]. Researchers have also been piloting the use of human voice to assist early diagnosis of a variety of illnesses: Parkinson's disease correlates with softness of speech (resulting from lack of coordination of the vocal muscles) [6,12], voice frequency with coronary artery disease (hardening of the arteries which may affect voice production) [19], and vocal tone, pitch, rhythm, rate, and volume correlate with invisible illnesses such as post-traumatic stress disorder [5], traumatic brain injury and psychiatric conditions [13]. The use of human-generated audio as a biomarker for various illnesses offers enormous potential for early diagnosis, as well as for affordable solutions which could be rolled out to the masses if embedded in commodity devices.…”
Section: Introductionmentioning
confidence: 99%
“…Research has now started to use digital technology to gather bodily sounds (e.g., digital stethoscopes) and run automatic analysis on the data [24], for example for wheeze detection in asthma [18,23]. Researchers have also been piloting the use of human voice to assist early diagnosis of a variety of illnesses: Parkinson's disease correlates with softness of speech (resulting from lack of coordination of the vocal muscles) [6,12], voice frequency with coronary artery disease (hardening of the arteries which may affect voice production) [19], and vocal tone, pitch, rhythm, rate, and volume correlate with invisible illnesses such as post-traumatic stress disorder [5], traumatic brain injury and psychiatric conditions [13]. The use of human-generated audio as a biomarker for various illnesses offers enormous potential for early diagnosis, as well as for affordable solutions which could be rolled out to the masses if embedded in commodity devices.…”
Section: Introductionmentioning
confidence: 99%
“…Study with enough evidence suggested that speech signals (such as certain vowel, words and numbers) contain vocal biomarkers that could be great aid to pathologist for the disease diagnosis. Several machine learning algorithms showed superior accuracy in disease prediction including Parkinson, depression, cardio and other diseases [38][39][40]. In the light of finding, it can be hypothesized that whether viral infections contain disease specific vocal biomarkers for disease analysis.…”
Section: Cov Outbreaks and Future Perspectivesmentioning
confidence: 99%
“…Motor symptoms include muscle stiffness, resting tremor, slow movement, and balance problems [5]. Nowadays, evidence exists that signs of PD can be identified through speech, and the analysis using machine learning techniques may help in the diagnosis [6].…”
Section: Introductionmentioning
confidence: 99%
“…The new position is defined by Equation (6). The bat algorithm is considered a frequency-tuning algorithm that provides a balanced combination of exploration and exploitation.…”
mentioning
confidence: 99%
See 1 more Smart Citation